2020
DOI: 10.1007/s42399-020-00541-4
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Review of the Anatomy of the Inferior Mesenteric Artery: Branching Patterns, Variant Anatomy and Clinical Significance

Abstract: The objective of this review is to describe the normal and variant anatomy of the inferior mesenteric artery (IMA), including a brief overview of the relevant embryology, as well as proposing a classification system of the IMA vasculature, and clinical significance. A systematic review of articles published in Google Scholar and PubMed database using search terms: inferior mesenteric artery anatomy, inferior mesenteric artery variation, inferior mesenteric artery development, mesenteric circulation anatomy and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 37 publications
1
11
0
1
Order By: Relevance
“…Among the 100 patients evaluated, the median age was 53.3 years, and 53% were men. In accordance with the McSweeney et al IMA classification system (5) , we identified type 1A in 9% of the patients, type 1B in 47%, type 1C in 24%, type 2 in 16%, and type 3 in 4%. As can be seen in Table 1, there were no statistically significant differences between men and women in terms of the frequency of the anatomical variations of the IMA (p = 0.04).…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Among the 100 patients evaluated, the median age was 53.3 years, and 53% were men. In accordance with the McSweeney et al IMA classification system (5) , we identified type 1A in 9% of the patients, type 1B in 47%, type 1C in 24%, type 2 in 16%, and type 3 in 4%. As can be seen in Table 1, there were no statistically significant differences between men and women in terms of the frequency of the anatomical variations of the IMA (p = 0.04).…”
Section: Resultssupporting
confidence: 82%
“…The branching pattern of this artery also varies among individuals, and there are few anatomical, angiographic, or surgical studies that support what is traditionally taught as normal in anatomy texts (3) . Although the origin of the IMA is fairly constant, the branching pattern of its arteries-the left colic artery (LCA), sigmoid trunk, and superior rectal artery-is highly variability in terms of the origin and number of those branches, as well as the presence or absence of secondary branches (4,5) . Identifying these variations is essential to devising preoperative strategies, in order to determine the arterial branching pattern, the knowledge of which is quite helpful to surgeons, who must make decisions regarding vessel resection and lymph node dissection, to avoid anastomotic complications (6)(7)(8) .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, several reviews have systematically reviewed the historical development of IMA classification and utilized meta-analysis to statistically evaluate the classical types [23][24][25]. The Yada and Zebrowski classifications seem to be the most widely applied; however, the Yada classification overlooks the description of the SA, and the Zebrowski classification is somewhat complex.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the pattern of the IMA and its branches were observed and classified according to the classification described by McSweeney et al 14 . We classified the branching patterns of the IMA into five types (1A, 1B, 1C, 2, and 3).…”
Section: Methodsmentioning
confidence: 99%